On the representation type of Jordan basic algebras - Kashuba, I.; Ovsienko, S.; Shestakov, I. (Algebra and Discrete Mathematics, 2017)
A finite dimensional Jordan algebra J over a field k is called basic if the quotient algebra J/RadJ is isomorphic to a direct sum of copies of k.
We describe all basic Jordan algebras J with (RadJ)²=0 of finite and tame representation type over an algebraically closed field of characteristic 0.